STUDI KELAYAKAN PEMBANGUNAN PUSAT PERBELANJAAN COKROAMINOTO - Sutika, I Kadek; Wiksuana, I G. B.; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study was concerned with the evaluation of investment plans of Tjokroaminoto Shopping Center planned by the Government of the City of Denpasar. Provision of facilities in the form of the construction of Shopping Center located at Tjokroaminoto, the Village of North Pemecutan, Denpasar. This study aimed to determine the feasibility of the development plan of government assets which would be revitalized to be Shopping Center from the legal, technical and management, market and marketing, social and financial aspects. The data was collected through observation and interview methods. The results of the feasibility study showed that the construction of Shopping Centre is feasible both from a legal, technical and management, market and marketing, and social and financial aspects. The assessment of the financial aspects was indicated by the ARR amounting to 50.32%; PP would be 4.6 years; Positive NPV totaled Rp 95,747,663,065; and PI was 1.83.
Keywords: Feasibility Study, ARR, PP, NPV, PI